Customer's new voice : - McKean, John (John Wiley & Sons, 2015)
The Customer's New Voice shows businesses how to motivate and transform directly volunteered consumer knowledge into profitable insights, enabling a new echelon of marketing relevancy, customer experience, and personalization. With a deep look at the inner workings of how a modern generation of business innovators are tapping into the fresh opportunities with the customer's new voice, this book describes how businesses are transforming "inference-based" predictions of purchase intent with direct consumer knowledge of their actual intentions and buying context. The result: An untouchable/unprecedented level of offer relevancy, experience, and personalized service levels.